Gating effects of conductive polymeric ionic liquids. Issue 30 (24th July 2018) - Chen, Senbin; Frenzel, Falk; Cui, Bin; Gao, Fang; Campanella, Antonella; Funtan, Alexander; Kremer, Friedrich; Parkin, Stuart S. P.; Binder, Wolfgang H.
Abstract : Poly(ionic liquid)s with different topologies are investigated towards the gating effects for the first time. Abstract : Poly(ionic liquid)s (POILs) belong to one of the most promising materials class in electrochemistry. In this study, we investigate POILs as a gating material within a field-effect transistor, additionally describing their glassy dynamics and charge transport properties. Four different imidazolium-based POILs have been investigated, ranging from homopolymers with varied counterions, i.e. POIL1 : P(APMIN(Tf)2 ) poly(1-[2-acryloylpropyl]-3-methylimidazolium bis(trifluoromethane)sulfonamide) and POIL2 : P(APMIPF6 ) poly(1-[2-acryloylpropyl]-3-methylimidazolium hexafluorophosphate, to semifluorinated random copolymers, i.e. POIL3 : P(APMIN(Tf)2 - co -TFEA) (TFEA: 2, 2, 2-trifluoroethyl acrylate), and finally to semifluorinated triblock copolymers, POIL4 : P(APMIN(Tf)2 - co -TFEA)- b -PPFS- b -P(APMIN(Tf)2 - co -TFEA) (PPFS: polypentafluorostyrene). Their glassy dynamics and charge transport mechanism are investigated by broadband dielectric spectroscopy (BDS), differential scanning calorimetry (DSC) and alternating current chip-calorimetry (ACC). The gating effects of these POILs are studied in detail, showing for the first time a reversible phase transition between thin films formed from the brownmillertite phase SrCoO2.5 and the perovskite phase SrCoO3 by use of such POILs, being especially pronounced for POIL1 : P(APMIN(Tf)2 ) homopolymer displaying gate voltages ( V G ) of 3–4 V and a gating time of ∼4 h. In the case of the POIL3, P(APMIN(Tf)2 - co -TFEA) as a random copolymer, higher V G (−8/+5 V) and a longer gating time (∼16 h) are revealed. Phase transition between SrCoO2.5 and SrCoO3 could not be observed from POILs2 &4 even using very large gate voltages (−10/+8 V) for a much longer time (48 h), indicating that primarily charge density and charge-carrier mobility are decisive in ionic liquid gating.